Peirce’s Suspended Second, and Art’s ’Ethical Phenomenology’ - Trimarchi, Nat (Cosmos and History: The Journal of Natural and Social Philosophy, 2024)
The fundamental problem for theoretical aesthetics is its inability to account for art’s meaning-value (Trimarchi, 2022). As previously argued, Art’s higher meaning is only found emerging from the artwork’s tacit dimensions, where empirical-historical intentionality is almost completely inconsequential (Trimarchi, 2024b). The latter’s interpretable ‘phenomenology of sequence’ produces a false theorising tendency, disconnecting art from the history of ideas and severing aesthetics from ethics and logic. Art appears ‘infinitely interpretable’, hence entirely subjective. Adapting Arnold’s (2011) actantial processual approach, I show how Peircian semiotics, via ‘real Secondness’, uncovers art’s higher meaning. Peirce’s ‘diagrammatic thinking’ exposes art’s unique role of ‘objectifying’ the Person (in any subject, via appropriate propositions), without de-valuing this bearer of moral values. His ‘semiotic realism’ helps unveil Scheler’s anthropological (also termed ‘ethical’) phenomenology emerging from Merleau-Ponty’s ‘obscure zone’, to discern poetic from other speculation. Art’s ‘subject-objectivation’ (or, ethical intentionality) is thus able to be mapped phenomenologically to reveal any artwork’s meaning-value orientation. This paper combines Peirce’s ‘phenomenology of reason’ with Scheler’s hierarchy of values and Schelling’s ‘mythological categories’ (Trimarchi 2024b) to suggest a methodology for moving beyond neo-Kantian theoretical aesthetics (and analytical philosophy’s grip on the anti-art of ‘modernity’). That is, moving from the realm of perception to knowing, reviving art’s ontological connection to normative aesthetics. In conclusion, Peirce’s ‘science of ideals’ is thus revealed as Complexity Science, which – via his ‘suspended second’ (or, Ricoeur’s ‘second ontology’) - vindicates Schelling’s claim for how ‘aesthetics becomes objective’ (Trimarchi, 2024a).